Characterization on MOF-based TFN membranes for metal ions separation and recovery - Ong, Jia Kang (Nanyang Technological University, 2024)
Metal-Organic Frameworks (MOFs) incorporated into Thin Film Nanocomposite (TFN) membranes as nanofillers present a viable way to improve the processes involved in the recovery and separation of metal ions. When compared to traditional methods, these membranes show enhanced selectivity, flux rates, and stability because MOFs are integrated into the polymeric matrix during membrane synthesis. Utilising advanced characterisation techniques like Thermal Gravimetric Analysis (TGA) and Zeta potential, the thermal and material properties of MOF-based TFN membranes, such as surface charge, wettability, and hydrophilicity/hydrophobicity, provides important insights into the membranes' performance. The goal of the study is to analyse the composition and structure of MOF-based TFN composites and how they affect the characteristics of membranes. The study also assesses how well-suited as-characterised TFN membranes are for applications involving the recovery and separation of metal ions. Through this study, a fundamental understanding of MOF-based TFN membranes will be achieved, which will aid in the creation of more effective and long-lasting techniques for the recovery and separation of metal ions.